The Relevance of Remittances in Fostering Economic Growth in the West Balkan Countries - Topxhiu, Rahmije Mustafa; Krasniqi, Florentina Xhelili (Ekonomika, 2017)
The remittances of diaspora workers, resulting from international migration, have attracted the attention of academics and policymakers for their role and importance in macroeconomic variables in their countries of origin. The purpose of the paper is to explore the effects of remittances and other variables, such as exports, capital formation, foreign direct investment, and labor force on economic growth in the six former Western Balkan communist countries (Albania, Kosovo, Macedonia, Montenegro, Bosnia and Herzegovina and Serbia). This study utilizes a strongly balanced panel data over the 2005-2015 period for the six Western Balkan countries using the ordinary least squares method (OLS), i.e., the Pooled Regression Model, to evaluate the parameters. According to the regression results, we can conclude that remittances have a positive impact on economic growth in the West Balkan countries, so remittances can foster economic growth in those countries. Also, we find a statistically significant positive relationship between economic growth and other variables included in the model, such as exports, capital formation, and labor. The relationship between economic growth and foreign direct investment has turned out to be statistically insignificant and negatively related.